(untitled) (Journal of Hama University, 2021)
The aim of this research is to uncover the role of the school principal as a resident educational supervisor from the teachers ’point of view in the first cycle of basic education in the city of Damascus. The research community consisted of (4208) teachers, and the study sample consisted of (480) male and female teachers, and to achieve the study goals the researcher Developing a tool to measure the role of the school principal as a resident educational supervisor from the teachers’ point of view, which is a paragraph on a questionnaire consisting of five fields comprising (53) paragraphs, The validity of the tool was verified by presenting it to the arbitrators, and for its stability by extracting the stability parameters, and the stability factor of Cronbach alpha reached (0.89). The educational qualification and training courses, and the results of the study resulted in the following: The school principal has a role as a highly resident educational supervisor, and the research fields are arranged according to the following order: (curriculum, professional development for teachers, teaching planning, classroom management, evaluation), as the study results showed - there were statistically significant differences at the level of significance ( ) The average score of study sample responses on the study tool according to the gender variable in favor of males - the presence of statistically significant differences according to the variable of the educational qualification in favor of university leave - the presence of statistically significant differences according to the variables of years of experience in favor of the two categories (less than 5 years, and the category more than 10 years ) - There is an escape S statistically significant variable depending on the training courses and the differences in favor of follow training courses.